2014
DOI: 10.1051/0004-6361/201220542
|View full text |Cite
|
Sign up to set email alerts
|

Standing sausage waves in photospheric magnetic waveguides

Abstract: Aims. By focussing on the oscillations of the cross-sectional area and the total intensity of magnetic waveguides located in the lower solar atmosphere, we aim to detect and identify magnetohydrodynamic (MHD) sausage waves. Methods. Capturing several high-resolution time series of magnetic waveguides and employing a wavelet analysis, in conjunction with empirical mode decomposition (EMD), makes the MHD wave analysis possible. For this paper, two sunspots and one pore (with a light bridge) were chosen as exampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 49 publications
4
51
1
Order By: Relevance
“…Such oscillations occur in propagating or standing states (Rosenthal et al 2002;Dorotovič et al 2014). The magnetic fields act as a guide for magnetohydrodynamics (MHD) waves effectively increasing the connection between different layers of the solar atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Such oscillations occur in propagating or standing states (Rosenthal et al 2002;Dorotovič et al 2014). The magnetic fields act as a guide for magnetohydrodynamics (MHD) waves effectively increasing the connection between different layers of the solar atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of highresolution observations from ground-and space-based instruments, both standing and propagating SMAWs have been discovered in a multitude of structures in the solar atmosphere including magnetic pores (Morton et al 2011;Dorotovič et al 2014;Moreels et al 2015;Freij et al 2016), chromospheric network (Vecchio et al 2007; Kontogiannis et al 2010Kontogiannis et al , 2014, coronal loops (Wang et al 2015;Jess et al 2016), and polar plumes (Krishna Prasad et al 2011;Su 2014). Recent multiwavelength observations of sunspots reveal that umbral flashes (Beckers & Tallant 1969;Rouppe van der Voort et al 2003) and running penumbral waves (Giovanelli 1972;Bloomfield et al 2007;Freij et al 2014) observed in the chromosphere, and quasi-periodic propagating disturbances observed in the coronal loops (Berghmans & Clette 1999;De Moortel et al 2000;De Moortel 2009), are just different manifestations of the SMAWs that propagate from the photosphere through to the corona (Jess et al 2012a;Krishna Prasad et al 2015;Zhao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…All of these are available with modern groundor space-based observations combined with empirical solar atmospheric models (e.g. recent work by Morton et al 2011;Dorotovič et al 2014;Moreels et al 2015). Our equations are generally valid and can be used to calculate the energy and energy flux in the observed axisymmetric waves.…”
Section: Energy Inside the Flux Tube For Body Modes And External Energymentioning
confidence: 99%
“…A&A 578, A60 (2015) In this paper we focus on axisymmetric slow and fast sausage modes, which have recently been discovered in numerous structures, but have not been adequately modelled to estimate their energy content. They have been detected in coronal loops (De Moortel et al 2000;Wang et al 2002Wang et al , 2003Krishna Prasad et al 2012), in photospheric pores (Dorotovič et al 2008(Dorotovič et al , 2014Morton et al 2011;Moreels et al 2015), in network bright points (McAteer et al 2003;Bharti et al 2006;Martínez González et al 2011), in flares (Nakariakov et al 2003;Melnikov et al 2005;Van Doorsselaere et al 2011), and in the chromosphere (Morton et al 2012a). Some authors have attempted to estimate the amount of energy present in these observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation